FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT MYRIA KOTA PALEMBANG - Lilik Pranata; Maria Tarisia Rini; Vincencius Surani (Universitas Baiturrahim, 2017)
Background:Job satisfaction is an emotional attitude that is fun and loves her job. This attitude is reflected by the morale of work, discipline and work pretation. Job satisfaction is enjoyed in work, out of work and in combination between the two. Methods: The aim of this research is to find out the correlation between the factors related to the work satisfaction of the nurses in the hospital ward of Myria Palembang Hospital. Using quantitative method of analytic survey with cross sectional approach. Using the questionnaire technique in data collection. Population of all implementing nurses working in the inpatient wards of Myria Palembang Hospital. The sample was 55 nurses using purposive sampling technique. Based on data analysis using chi square test in get result of this research indicate existence of relation of work motivation with job satisfaction of nurse, with p value 0.008 <α 0,05. Result :The existence of relation between work environment condition with job satisfaction of nurse, with p value 0,000 <α 0,05. No relationship with manager role with nurse job satisfaction, with p value 0,209> α 0,005.Conclusion: Based on the results of research suggested to the place of research to pay more attention and improve nurse job satisfaction, by creating good relationships among employees.